Analysis of Factors that Influence Student Consumptive Behavior - Tjane, Moh. Fachry Zhen; Ahmad, M. Ihsan Said; Rahmatullah; Nurjannah; Ampa, Andi Tenri (Universitas Negeri Semarang, 2024)
Purchasing or using goods or services solely to satisfy desires and needs without considering the benefits and needs is known as consumerism. The research is aimed at testing and analyzing several variables of consumer behavior, including family social and economic status, peer groups, and economic literacy. Quantitative methods are used, and data is collected through observations, questionnaires, and documentation. This research involved a sample of 80 students. Double linear regression is used to analyze data. The results of the study showed that the socio-economic status of the family has a positive and significant impact on the consumer behavior of the students; the factors of the peer group have a positive impact as well as a significant influence on the student's consumptive behavior; and the economic literacy factors have a negative impact that significantly influences the students' consumer behavior.